Particle swarm optimization of air-cored axial flux permanent magnet generator for small-scale wind power systems - Xia, Bing; Luk, Patrick Chi-Kwong; Fei, Wei-Zhong; Yu, L. (Institution of Engineering and Technology (IET), 2014)
Axial flux permanent magnet synchronous machines with aircored configuration is particular suitable for small scale wind power system due to their advantages of low synchronous reactance, cogging torque free, high efficiency and high power factor. However, due to the number of machine parameters, with some tightly `coupled' with each other, optimisation of the design could become extremely challenging by conventional analytical means. Here, the particle swarm optimization method is used in the design of an axial flux permanent magnet generator for small-scale wind power system. Five inter-dependent design parameters are adjusted simultaneously to achieve an optimal solution for the application. Three-dimensional finite element analysis is employed to evaluate the electromagnetic performance for the optimization. The results show the proposed optimization method is efficient and with fast convergence.
Keywords: Air-cored; axial flux permanent magnet; particle swarm optimization; wind power